Effect of Iron II on Hydroxyapatite Dissolution and Precipitation in vitro - Delbem, Alberto Carlos Botazzo [UNESP]; Alves, K. M. R. P. [UNESP]; Sassaki, K. T. [UNESP]; Moraes, João Carlos Silos [UNESP] (Karger, 2012)
The aim of this study was to evaluate the effect of iron II on the dissolution and precipitation of synthetic hydroxyapatite (HA). HA powder was suspended in solutions of iron (0.84 mu g/ml, Fe0.84; 18.0 mu g/ml, Fe18; 70.0 mu g/ml, Fe70), fluoride (1,100 mu g/ml, F1,100), and deionized water and submitted to pH cycling. After pH cycling, the samples were analyzed by infrared spectroscopy and X-ray diffraction. The concentrations of fluoride, calcium, phosphorus, and iron were also analyzed. The data were submitted to ANOVA, and analyzed by Tukey's test (p < 0.05). The infrared spectrum showed a reduction in all bands corresponding to phosphates and hydroxyls and an increase in the carbonate band in the groups with iron. The intensity of the phosphate bands increased and that of the hydroxyl bands decreased in the group F1,100.1t was observed that there was a higher concentration of Ca in the group F1,100, with no significant difference between the groups Fe18 and Fe70 (p > 0.05). There was an increase in Fe concentration in the HA directly related to the Fe concentration of the treatment solutions. Results show that the presence of Fe causes the precipitation of apatite with high solubility. Copyright (C) 20125. Karger AG, Basel
Keywords: Calcium; Chemical analysis; Fluoride; Hydroxyapatite; Iron